Ultimate Bearing Capacity of Strip Footing on Sand Underlain By Clay Under Inclined Load - Dutta, Rakesh Kumar; Khatri, Vishwas Nandkishor; Kaundal, Nitesh (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the bearing capacity determination of strip footing placed on sand underlain by clay and subjected to inclined loading. The bearing capacity equation is derived within the framework of limit equilibrium by following the projected area approach. The inclinations of load spread were selected by performing an additional finite element analysis.
Keywords: strip footing; bearing capacity; layered soils; load; ława fundamentowa; nośność; grunt wielowarstwowy; obciążenie